New Earth-Abundant Thin Film Solar Cells Based on Chalcogenides - Le Donne, Alessia; Trifiletti, Vanira; Binetti, Simona (Frontiers in Chemistry, 2019)
At the end of 2017 roughly 1.8% of the worldwide electricity came from solar photovoltaics (PV), which is foreseen to have a key role in all major future energy scenarios with an installed capacity around 5 TW by 2050. Despite silicon solar cells currently rule the PV market, the extremely more versatile thin film-based devices (mainly Cu(In,Ga)Se2 and CdTe ones) have almost matched them in performance and present room for improvement. The low availability of some elements in the present commercially available PV technologies and the recent strong fall of silicon module price below 1 $/Wp focused the attention of the scientific community on cheap earth-abundant materials. In this framework, thin film solar cells based on Cu2ZnSnS4 (CZTS) and the related sulfur selenium alloy Cu2ZnSn(S,Se)4 (CZTSSe) were strongly investigated in the last ten years. More recently, chalcogenide PV absorbers potentially able to face TW range applications better than CZTS and CZTSSe due to the higher abundance of their constituting elements are getting considerable attention. They are based on both MY2 (where M= Fe, Cu, Sn and Y=S and/or Se) and Cu2XSnY4 (where X= Fe, Mn, Ni, Ba, Co, Cd and Y=S and/or Se) chalcogenides. In this work, an extensive review of emerging earth-abundant thin film solar cells based on both MY2 and Cu2XSnY4 species is given, along with some considerations on the abundance and annual production of their constituting elements.